Current challenges surrounding exosome treatments - Eileen Tzng; Nathan Bayardo; Phillip C. Yang (Extracellular Vesicle)
Cardiovascular disease is the leading cause of death worldwide today and numerous studies are demonstrating that exosomes improve cardiac function after myocardial injury through various mechanisms. Exosome therapy has great potential as an effective precision medicine biologic by targeting the underlying disease process. However, this innovative approach may face some challenges, such as zeta potential, standardization of exosome collection, biopharmaceutical regulation, and more importantly, specific clinical application of exosome therapy. These issues will be addressed by broadly summarizing the biological plausibility; delivery, dosing, and pharmacokinetics; and reproducibility and manufacturing with a focus on microRNA as molecular cargo.